Initial Experience of Transesophageal Echocardiography in NAMS Bir Hospital - Shah, Ram Kishor (Nepalese Heart Journal, 2013)
A retrospective study of patients undergoing trans esophageal echocardiogram was conducted in Bir Hospital, from April 2008 to March 2010. A total of 51 patients were included in the study. Among the 51 patients 29 (56.8%) were female and 22 (43.2%) were male. Mean age was 38 +/- 15.1 (range 12-77 years). The improved resolution and anatomic detail provided by TEE makes it such a powerful diagnostic tool. TEE is a safe outpatient procedure. Viscous two percent lidocaine topical anesthesia was adequate for the procedure. Common indication for TEE was to confirm Atrial septal defect and Left atrial clot. Complications of TEE were very few. In this study most common problems were nausea and vomiting in 22 cases (43.1%) during procedure. Sore throat was in 3 cases(5.8%) after the procedure. Ventricular premature contractions were seen in I case(1.9%). Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 44-47 DOI: http://dx.doi.org/10.3126/njh.v7i1.8502